KARAKTERISTIK DAN MOTIVASI WISATAWAN DALAM VOLUNTOURISM DI KABUPATEN GIANYAR (Studi Kasus Pada Yayasan Widya Guna Desa Bedulu dan Yayasan Bumi Sehat Desa Nyuh Kuning) - Irena Hersi Kristanti; Ni Made Oka Karini; I Putu Sudana (Department of Tour and Travel Studies, Faculty of Tourism, Udayana University, 2015)
Nowadays social motivation appears in various forms of tourism activities, one of them is the presence of voluntourism activities in a foundation or village where tourist activity could bring sustainable positive impact for nature and local communities. In this study, the author is interested to collect the data about the characteristics and motivations of volunteer tourists on voluntourism in Widya Guna Foundation, Bedulu Village and Bumi Sehat Foundation, Nyuh Kuning Village, Gianyar Regency, Bali. The purpose of this study is to determine how the characteristics and motivations of volunteer tourists in both foundation in order to inspire other tourists in a choice of responsible tourism. Methods of data collection which been used were observation, questionnaire, interview, and literature study. The results obtained by the data collection are that the characteristics of the volunteer tourists are divided into trip descriptor and tourist descriptor. Based on those descriptors, the volunteer tourists of Widya Guna and Bumi Sehat foundations are classified as discoverers, educators, and learners, befrienders, and investors. Motivations of volunteer tourists are divided into intrinsic motivations and extrinsic motivations. Intrinsically, their motivations are fulfilling a dream, personal growth, and professional development. While extrinsically are the attraction of travel or adventure places around the foundations, cultural exchange/learning, and a chance of broadening horizons. Recommended to governments, local communities, the inhabitants of the foundation, and the volunteer tourists to carry out their respective roles well and comply with the existing regulations in order to create the good impact of voluntourism activities for all parties concerned.